1981
DOI: 10.1093/ajcn/34.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Essential fatty acid status in cystic fibrosis and the effects of safflower oil supplementation

Abstract: The fatty acid compositions of serum phospholipids, cholesteryl esters, triglycerides, and free fatty acids were determined on a group of cystic fibrosis patients. These were compared with similar data from random hospitalized patients of the same age groups of both sexes. Fatty acid patterns in all lipid classes were skewed in the direction of essential fatty acid deficiency, but the differences were most dramatic in phospholipids. Many calculated parameters useful as indices of essential fatty acid status in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
64
0
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 22 publications
9
64
0
1
Order By: Relevance
“…Abnormalities in cord blood EFA in infants with CF suggest that a fundamental defect of fat metabolism may be in part responsible for the clinical manifestations of this disease (22). Several investigators have reported abnormalities of prostaglandin metabolism in CF patients (2,4).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in cord blood EFA in infants with CF suggest that a fundamental defect of fat metabolism may be in part responsible for the clinical manifestations of this disease (22). Several investigators have reported abnormalities of prostaglandin metabolism in CF patients (2,4).…”
Section: Discussionmentioning
confidence: 99%
“…Lloyd-Still et al (7) fed oral safflower oil (1 g/ kg/day) to 11 CF patients for 1 yr, but was unable to correct 18:2 deficiency and or to produce a significant change in sweat chloride concentration or sweat rate; there was also no clinical improvement when compared to a control group. Chase et al (34), in a double-blind study of twice monthly infusions of Intralipid, found clinical improvement of the supplemented children when compared to controls; however, 2 wk after each infusion, plasma and RBC linoleic acid levels were not increased.…”
Section: Discussionmentioning
confidence: 99%
“…Altered plasma and tissue concentrations of fatty acids in cystic fibrosis (CF) 4 patients have been well described (1)(2)(3)(4)(5)(6)(7). Changes in concentrations of selected essential fatty acids have been found in CF patients, notably decreases in the plasma and tissue concentrations of linoleic acid (18:2 n-6) and docosahexaenoic acid (DHA; 22:6 n-3).…”
Section: © 2007 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Changes in concentrations of selected essential fatty acids have been found in CF patients, notably decreases in the plasma and tissue concentrations of linoleic acid (18:2 n-6) and docosahexaenoic acid (DHA; 22:6 n-3). Increases in the concentration of eicosatrienoic acid (Mead acid; 20:3 n-9) have been identified in several studies (5)(6)(7). These alterations in fatty acid concentrations are significantly magnified in patients with severe variations in the CF transmembrane conductance regulator (CFTR) 5 gene, suggesting an association between the basic defect and abnormal essential fatty acid metabolism in CF patients (3 ).…”
Section: © 2007 American Association For Clinical Chemistrymentioning
confidence: 99%